Systemic inseticides in the control of Elasmopalpus lignosellos and their effect on soybeans - Heinrichs, Elvis A. (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was conducted at the Agronomy Research Station of the Federal University of Rio Grande de Sul, at Guaíba, RS, with the objective of determining the effectiveness of several chemical treatments on the control of the lesser cornstalk bares, Elasmopalpus lignosellus (Zeller 1848). Treatments consisted of 2 rates each of Carbofuran, Aldicarb, and Disulfoton as in-furrow granular treatment, carbofuran as a seed treatment and 2 treatments consisting of 1 and 3 applications of Endrin as a post-emergence spray. Results indicated only the 2 Endrin treatments as providing control of E. lignosellus. High grain yields in the Endrin and Carbofuran granular treatments were attributed to control of the leaf feeding caterpillar, Anticarsia gemmatalis Hübner (1818) as based on defoliation estimates. The only adverse treatment effect was a decrease in number of Rhizobium nodules/plant when Carbafuran was applied as a seed treament at the rate of 10 g/kg of seeds.